Photoaquation mechanism of hexacyanoferrate(II) ions: ultrafast 2D UV and transient visible and IR spectroscopies - Reinhard, Marco; Auböck, Gerald; Besley, Nicholas A.; Clark, Ian P.; Greetham, Gregory M.; Hanson-Heine, Magnus W.D.; Horvath, Raphael; Murphy, Thomas S.; Penfold, Thomas J.; Towrie, Michael; George, Michael W.; Chergui, Majed (American Chemical Society, 2017)
Ferrous iron(II) hexacyanide in aqueous solutions is known to undergo photoionization and photoaquation reactions depending on the excitation wavelength. To investigate this wavelength dependence, we implemented ultrafast two-dimensional UV transient absorption spectroscopy, covering a range from 280 to 370 nm in both excitation and probing, along with UV pump/visible probe or time-resolved infrared (TRIR) transient absorption spectroscopy and density functional theory (DFT) calculations. As far as photoaquation is concerned, we find that excitation of the molecule leads to ultrafast intramolecular relaxation to the lowest triplet state of the [Fe(CN)6]4– complex, followed by its dissociation into CN– and [Fe(CN)5]3– fragments and partial geminate recombination, all within <0.5 ps. The subsequent time evolution is associated with the [Fe(CN)5]3– fragment going from a triplet square pyramidal geometry, to the lowest triplet trigonal bipyramidal state in 3–4 ps. This is the precursor to aquation, which occurs in ∼20 ps in H2O and D2O solutions, forming the [Fe(CN)5(H2O/D2O)]3– species, although some aquation also occurs during the 3–4 ps time scale. The aquated complex is observed to be stable up to the microsecond time scale. For excitation below 310 nm, the dominant channel is photooxidation with a minor aquation channel. The photoaquation reaction shows no excitation wavelength dependence up to 310 nm, that is, it reflects a Kasha Rule behavior. In contrast, the photooxidation yield increases with decreasing excitation wavelength. The various intermediates that appear in the TRIR experiments are identified with the help of DFT calculations. These results provide a clear example of the energy dependence of various reactive pathways and of the role of spin-states in the reactivity of metal complexes.